Rheological behavior of starch/carrageenan/milk proteins mixed systems: Role of each biopolymer type and chemical characteristics. (December 2017) - Agoda-Tandjawa, G.; Le Garnec, C.; Boulenguer, P.; Gilles, M.; Langendorff, V.
Abstract: In this study, rheological synergistic consequences of starch/carrageenan/milk proteins mixed systems were investigated by considering the role of each biopolymer type as well as their intrinsic characteristics. Through this study, we showed that starch endogenous proteins have no impact on the viscoelastic properties of starch/carrageenan mixed systems in presence or not of milk proteins. However, these properties were seen to be strongly dependent on the type of gelling carrageenans. Indeed, the ι-carrageenan-based systems led to lower viscoelastic properties compared to the κ-carrageenan-based systems, mainly due to the conformational ordering and the network characteristics of each gelling carrageenan-type. It was also demonstrated that whatever the type of gelling carrageenans, swollen starch granules filled in carrageenan gel network led to improved viscoelastic properties in comparison to pure carrageenan gels; the resulting filled composite gel strength becoming most pronounced in presence of milk proteins. This important reinforcement of the carrageenan gel networks in presence of both swollen starch granules and milk proteins appeared to be preferentially driven by the exclusion effect of swollen starch granules as well as their role as "filler". In addition, the dominant role of the exclusion phenomenon of swollen starch granules became limited upon increasing carrageenan concentration in the mixed system; this effect being slightly less pronounced in presence of milk proteins. Finally, in terms of structural organization, the ternary mixed system can be regarded as a filled composite gel in which carrageenan chains and casein micelles form a three-dimensional hybrid network filled and strengthened by swollen starch granules. Graphical abstract: Highlights: Viscoelastic properties of starch/carrageenan/milk proteins mixed systems were investigated. κ-carrageenan/starch milk gels exhibited higher viscoelastic properties than those prepared with ι-carrageenan. Outstanding rheological synergy was obtained for starch/carrageenan/milk proteins mixed gels. Carrageenan chains and casein micelles form a three-dimensional hybrid network filled and strengthened by swollen starch granules.